PEMBERDAYAAN DAN PEMBINAAN MASYARAKAT EKONOMI LEMAH DI LINGKUNGAN IV KELURAHAN SIDOMULIO KECAMATAN MEDAN TUNTUNGAN - Anton A. P. Sinaga; Henri Saragih; Elperida J. Sinurat; Maludin Panjaitan; Jon Henri Purba; Anggiat P. Tambunan; Hotlan Butarbutar; Junika Napitupulu; Kristanty M. N. Nadapdap; Mangasa Panjaitan; Mislan Sihite (Universitas Methodist Indonesia, 2021)
The purpose of community service activities in the form of Empowerment and Fostering of Weak Economic Communities is to provide input on what businesses can be developed according to the conditions in the environment and in accordance with the current situation, namely the Covid 19 Pandemic outbreak. The target audience in this PPM activity are people who live in Neighborhood IV, Sidomulio Village, Medan Tuntungan District, totaling 25 people whose livelihoods are as farmers and also as farm laborers. The availability of adequate academics in giving lectures on Empowerment and Development of Weak Economic Communities at the Management Study Program, Faculty of Economics, Indonesian Methodist University, the enthusiasm of the participants, the support of the Village Head and the Head of the Environment for the implementation of activities and supporting funds from UMI are the supporters of the implementation of this PPM activity. The problem is the limited time for coaching. The benefits that participants get from this PPM activity include fostering economically weak communities.